De Novo DNM1L Variant in a Teenager With Progressive Paroxysmal Dystonia and Lethal Super-refractory Myoclonic Status Epilepticus. (September 2018) - Ryan, Conor S.; Fine, Anthony L.; Cohen, Alexander L.; Schiltz, Brenda M.; Renaud, Deborah L.; Wirrell, Elaine C.; Patterson, Marc C.; Boczek, Nicole J.; Liu, Raymond; Babovic-Vuksanovic, Dusica; Chan, David C.; Payne, Eric T.
Background: The dynamin 1-like gene ( DNM1L ) encodes a GTPase that mediates mitochondrial and peroxisomal fission and fusion. We report a new clinical presentation associated with a DNM1L pathogenic variant and review the literature. Results: A 13-year-old boy with mild developmental delays and paroxysmal dystonia presented acutely with multifocal myoclonic super-refractory status epilepticus. Despite sustained and aggressive treatment, seizures persisted and care was ultimately withdrawn in the context of extensive global cortical atrophy. Rapid trio-whole exome sequencing revealed a de novo heterozygous c.1207C>T (p.R403C) pathogenic variant in DNM1L . Immunofluorescence staining of fibroblast mitochondria revealed abnormally elongated and tubular morphology. Conclusions: This case highlights the diagnostic importance of rapid whole exome sequencing within a critical care setting and reveals the expanding phenotypic spectrum associated with DNM1L variants. This now includes progressive paroxysmal dystonia and adolescent-onset super-refractory myoclonic status epilepticus contributing to strikingly rapid and progressive cortical atrophy and death.